The Comparison of Gestational Diabetes Mellitus Screening between the One Step Method and the Two Step Method - Arini Estiastuti1, Deviana Soraya Riu1, Nur Rakhmah1, St. Maisuri T. Chalid1, Nugraha Utama Pelupess (Institute of Medico-legal Publications Pvt Ltd, 2020)
This research aimed to compare the results of gestational diabetes mellitus (DMG) screening based on theOne Step and Two Step method. This research was a cross-sectional study conducted in pregnant women24-28 weeks of gestation who meet the research criteria. The diagnosis of gestational diabetes using theOne Step and Two Step method was each carried out on 53 pregnant women so that the total sample ofthe research was 106 pregnant women. The results showed that 28.3% of pregnant women (15/53) werediagnosed with DMG with the One Step method compared with 3.8% (2/53) of pregnant women diagnosedby the Two Step method. There was a significant difference (p <0.05) between the diagnosis results ofthe two DMG diagnosis method. Further analysis of DMG risk factors showed that the highest positivelikelihood ratio (LR +) was found in the history of macrosomia with LR + = 4.45 with the One Step methodwhile the highest LR + for the Two Step method was found in obesity factors for pregnant women withLR + = 6.57. The highest positive predictive value (PPV) for the One Step method of 46.70% was foundin pregnant women with risk factors for obesity while the Two Step method was found in pregnant womenwith a history of DM (PPV = 100%). Pregnant women diagnosed with DMG were significantly greater in theOne Step method than the Two Step method. History of macrosomia (is found) as a risk factor for pregnantwomen diagnosed with DMG with the One Step method, while a history of DM for the Two Step method.